Hypocalcemia and Hypophosphatemia following Concurrent Denosumab Injection and Ferric Carboxymaltose Infusion in a Patient with Normal Renal Function - Naomi Szwarcbard; Chloe Dawson; Lai-Ming Kathleen Pak; Kathryn L. Hackman (Case Reports in Endocrinology)
Hypocalcemia following denosumab administration is well described. Hypophosphatemia following an intravenous iron infusion is an increasingly recognized adverse effect. Intravenous iron preparations increase fibroblast growth factor 23 (FGF23) levels. This both stimulates renal phosphate excretion and reduces 1,25-dihydroxyvitamin D (1,25(OH)2D) levels, resulting in reduced calcium absorption. Both osteoporosis and iron deficiency are common and frequently co-occur. The convenience and efficacy of both denosumab, a subcutaneous injection, and ferric carboxymaltose (Ferinject®), a 15-minute intravenous infusion, both of which can be given in the primary care setting, make these preferred treatment options. However, prescribers are often unaware of potential adverse outcomes, especially when these medications are given in tandem. We present a case of symptomatic hypocalcemia and hypophosphatemia in a 29-year-old woman with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) and normal renal function, in the setting of concurrent denosumab and ferric carboxymaltose administration for treatment of glucocorticoid-induced osteoporosis and iron deficiency anemia.